Glacial history of the Åsgardfonna Ice Cap, NE Spitsbergen, since the last glaciation - Allaart, Lis; Schomacker, Anders; Larsen, Nicolaj K.; Nørmark, Egon; Rydningen, Tom Arne; Farnsworth, Wesley R.; Retelle, Michael J.; Brynjólfsson, Skafti; Forwick, Matthias; Kjellman, Sofia Elisabeth (Quaternary Science Reviews, 2020)
The response of glaciers and ice caps to past climate change provides important insight into how they will react to ongoing and future global warming. In Svalbard, the Holocene glacial history has been studied for many cirque and valley glaciers. However, little is known about how the larger ice caps in Svalbard responded to Late Glacial and Holocene climate changes. Here we use lake sediment cores and geophysical data from Femmilsjøen, one of Svalbard’s largest lakes, to reconstruct the glacial history of the Åsgardfonna Ice Cap since the last deglaciation. We find that Femmilsjøen potentially deglaciated prior to 16.1 ± 0.3 cal ka BP and became isolated from the marine environment between 11.7 ± 0.3 to 11.3 ± 0.2 cal ka BP. Glacial meltwater runoff was absent between 10.1 ± 0.4 and 3.2 ± 0.2 cal ka BP, indicating that Åsgardfonna was greatly reduced or disappeared in the Early and Middle Holocene. Deposition of glacial-meltwater sediments re-commenced in Femmilsjøen at c. 3.2 ± 0.2 cal ka BP, indicating glacier re-growth in the Femmilsjøen catchment and the onset of the Neoglacial. The glacier(s) in the Femmilsjøen catchment area reached sizes no smaller than their modern extents already at c. 2.1 ± 0.7 cal ka BP. Our results suggest that larger Svalbard ice caps such as Åsgardfonna are very sensitive to climate changes and probably melted completely during the Holocene Thermal Maximum. Such information can be used as important constraints in future ice-cap simulations.